2017
DOI: 10.1021/acs.energyfuels.7b02053
|View full text |Cite
|
Sign up to set email alerts
|

Slagging and Fouling Characteristics of Zhundong High-Sodium Low-Rank Coal during Circulating Fluidized Bed Utilization

Abstract: Zhundong coal (ZDc) with a large reserve is faced with severe slagging and fouling during combustion in pulverized coal furnaces because of its high Na content. Due to the low-temperature reaction characteristics of a circulating fluidized bed (CFB), the ash-related problems might be alleviated when ZDc is used as fuel in a CFB. In this study, the slagging and fouling characteristics of three types of ZDc were tested in a 0.4 t/d CFB test system. The influences of three aspects including reaction temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, the process was still a major challenge because of the diversity of fuels. Song et al 17,18 carried out extensive work on the utilization of ZD coal in a CFB. The results showed that reaction temperature, reaction atmosphere and coal properties had considerable influences on the ash deposition characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the process was still a major challenge because of the diversity of fuels. Song et al 17,18 carried out extensive work on the utilization of ZD coal in a CFB. The results showed that reaction temperature, reaction atmosphere and coal properties had considerable influences on the ash deposition characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of slagging in the furnace increased as a function of the reaction temperature during gasification. 17 Under combustion conditions, the fouling on heating surfaces at medium temperatures (607–735 °C) was the main ash-related problem. 18 However, the influence of the combustion temperature on fouling is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 b shows the weight of slags deposited on the slagging probe during the CFBG of SHc. 36 The weight of slags deposited directly reflects the slagging degree. According to the weight of slags, it is inferred that the CFBG process of SHc is free from slagging at 900 °C because the weight of slags is almost zero.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of the slag hinders the heat transfer, which reduces the boiler thermal efficiency. 12,13 In addition, there are some corrosive components in the ash slag that cause corrosion and damage to the boiler, which directly threaten the safe operation of the power plant boiler. 14 Given the above problems, the combustion technology of liquid slag removal boiler possesses high combustion intensity, high slag removal rate, and low dust content in flue gas, which is particularly suitable for slagging coal.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhundong coal is prone to slagging due to its high content of alkali metals. The existence of the slag hinders the heat transfer, which reduces the boiler thermal efficiency 12,13 . In addition, there are some corrosive components in the ash slag that cause corrosion and damage to the boiler, which directly threaten the safe operation of the power plant boiler 14 .…”
Section: Introductionmentioning
confidence: 99%